(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
Knowledge is understood as a process through which the subject apprehends reality. It requires logical principles such as coherence, along with rigor and precision, in order to attain a scientific character. Yet, in the pursuit of objectivity, the subject has often been eclipsed in favor of the object alone. Science, essentially quantitative, excludes subjective representations and instead seeks to uncover the laws that govern structures and organization. This study explores the determinants and principles that shape the construction of knowledge across different historical paradigms. In antiquity, knowledge was marked by the primacy of metaphysics over physics, grounded in the notion of a First Principle as the ultimate cause of all plurality and diversity an ontologization of knowledge, where knowing meant tracing phenomena back to their first cause. By contrast, modern thought abandons essences and first causes, privileging facts and states of affairs expressed symbolically, most notably through mathematics. Scientific knowledge thus emerges as quantitative, privileging the observable and measurable while marginalizing the subject and cultural representations. Such a reduction of knowledge to quantification raises critical questions about the role of subjectivity and cultural frameworks in knowledge acquisition. This reduction has contributed to a form of mental colonization, whereby the theoretical schemas of the subject are subsumed under universalized scientific laws. The transition from macrophysics to microphysics has not fundamentally altered this absolutism. For Bachelard, it is reality—not reason that bears contradictions and controversies; science merely translates reality into rational language. By positing a “scientific noumenon,” Bachelard reveals how the dominance of a singular rationalism hinders the flourishing of diverse modes of rationality. Consequently, rational pluralism risks collapsing into a monologue, reinforcing a Eurocentric logos that asserts itself by denying alternative forms of thought.